Pengaruh Perputaran TATO, Rasio Lancar dan DAR Atas ROE pada Perusahaan Industri Barang Konsumsi di BEI 2015 – 2019 - Sufika Sary; Laura Denita; Aprilda Aprilda; Cynthia Cynthia (IPB University, 2021)
The purpose of this analysis is to explain how the impact of TATO, Current Ratio, DAR on ROE on the consumer goods industry on the IDX during 2015-2019. The total population is 58 with 26 companies as the sample. Techniques and data analysis in this study using purposive sampling, multiple linear regression analysis and classical hypothesis testing. This can be seen from the results of the study that simultaneously TATO, Current Ratio, DAR have an effect but not significant on ROE in consumer goods industrial companies listed on the IDX 2015-2019 with the results Fcount> Ftable (7,760> 2,68). Partially, TATO has a significant effect on ROE, with the result tcount <ttable (3,753> 1,97897). Current ratio has no and insignificant effect on ROE while DAR has no significant effect on ROE. The result of adjusted R-squared 0.136 or the coefficient of determination of 13,6% percent of the dependent variable ROE which can be explained by the independent variables TATO, Current Ratio, and DAR.